Twelve tips for medical curriculum design from a cognitive load theory perspective. (2nd July 2016) - Leppink, Jimmie; Duvivier, Robbert
Abstract: During their course, medical students have to become proficient in a variety of competencies. For each of these competencies, educational design can use cognitive load theory to consider three dimensions: task fidelity: from literature (lowest) through simulated patients (medium) to real patients (highest); task complexity: the number of information elements in a learning task; and instructional support: from worked examples (highest) through completion tasks (medium) to autonomous task performance (lowest). One should integrate any competency into a medical curriculum such that training in that competency facilitates the students' journey that starts from high instructional support on low-complexity low-fidelity learning tasks all the way to high-complexity tasks in high-fidelity environments carried out autonomously. This article presents twelve tips on using cognitive load theory or, more specifically, a set of four tips for each of task fidelity, task complexity, and instructional support, to achieve that aim.